Experience of wrong site surgery and surgical marking practices among clinicians in the UK. Issue 5 (30th October 2006) - Giles, Sally J; Rhodes, Penny; Clements, Gill; Cook, Gary A; Hayton, Ruth; Maxwell, Melanie J; Sheldon, Trevor A; Wright, John
Abstract : Background: Little is known about the incidence of "wrong site surgery", but the consequences of this type of medical error can be severe. Guidance from both the USA and more recently the UK has highlighted the importance of preventing error by marking patients before surgery. Objective: To investigate the experiences of wrong site surgery and current marking practices among clinicians in the UK before the release of a national Correct Site Surgery Alert. Methods: 38 telephone or face-to-face interviews were conducted with consultant surgeons in ophthalmology, orthopaedics and urology in 14 National Health Service hospitals in the UK. The interviews were coded and analysed thematically using the software package QSR Nud*ist 6. Results: Most surgeons had experience of wrong site surgery, but there was no clear pattern of underlying causes. Marking practices varied considerably. Surgeons were divided on the value of marking and varied in their practices. Orthopaedic surgeons reported that they marked before surgery; however, some urologists and ophthalmologists reported that they did not. There seemed to be no formal hospital policies in place specifically relating to wrong site surgery, and there were problems associated with implementing a system of marking in some cases. The methods used to mark patients also varied. Some surgeons believed that marking was a limited method of preventing wrong site surgery and may even increase the risk of wrong site surgery. Conclusion: Marking practices are variable and marking is not always used. Introducing standard guidance on marking may reduce the overall risk of wrong site surgery, especially as clinicians work at different hospital sites. However, the more specific needs of people and specialties must also be considered.